Analysis of the drying process for precursors of Cu2ZnSn(S, Se)4 layers by low cost non vacuum fabrication technique. (August 2021) - Punathil, Prabeesh; Zanetti, Solidea; Artegiani, Elisa; Kumar, Vikash; Romeo, Alessandro
Graphical abstract: Highlights: Low cost fabrication process without application of dangerous H2 S. For the first time drying times of the precursors are being analyzed. The drying time of the precursors affect the stoichiometry of the absorber. Efficiencies are influenced by the drying time of the absorber. Abstract: Cu2 ZnSn(S, Se)4 solar cells were fabricated by a non-vacuum solution-based spin coating technique followed by annealing in selenium atmosphere without H2 S treatment. The effects of the drying time after spin coating on physical and electrical properties of the cells were investigated. Structural and morphological properties were investigated by X-ray diffraction, Raman spectroscopy, energy dispersive X-ray analysis, atomic force microscopy and scanning electron microscopy. The physical properties, in terms of stoichiometry, crystal structure, morphology and orientation of the grains were shown to be influenced by the different drying times. Consequently, current–voltage characteristics show that the drying time of the precursors has a significant involvement in the device performance. The highest efficiency has been measured for 5 min drying time (with a 4.73% efficiency is obtained with Voc = 320 mV, Jsc = 28.6 mA/cm 2 and FF = 52%), while samples with longer or shorter drying time have lower efficiencies. A further increase in efficiency, exceeding 5%, is obtained by inserting a contact grid on the front contact. Also accelerated stability tests (performed in a black box with one sun illumination at 80 °C) show different effects in light soaking, almost no degradation is observed for all the three cases. In this paper we highlight the connection of the different physical to the electrical properties generated just by the different drying times of the precursor for the CZTS absorbers.